Participation and Capacity of Officials in Drafting Village Regulations: Partisipasi dan Kapasitas Aparatur dalam Penyusunan Peraturan Desa - Hananto Widodo; Intan Lovisonnya; Irfa Ronaboyd; Elisabeth Septin Puspoayu; Viona Aristanti; Mutiara Ayu Lestari (Universitas Muhammadiyah Sidoarjo, 2025)
Background (General): Governance at the village level plays a vital role in realizing democratic principles and sustainable local development, particularly within the framework of decentralization in Indonesia. Background (Specific): Desa Rogojampi in Banyuwangi faces challenges in implementing village regulations (Perdes) due to limited institutional capacity, low community participation, and suboptimal oversight mechanisms. Knowledge Gap: Although the legal framework strongly supports village autonomy, empirical evidence on how regulatory formulation aligns with good governance principles at the village level remains insufficient. Aims: This study aims to analyze perceptions of villagers, local officials, and the Village Consultative Body (BPD) regarding the formulation of Perdes as an instrument to strengthen good governance. Results: A survey of 40 respondents revealed adequate public understanding of Perdes (72%), but participation in drafting remains low (58%). Village officials’ regulatory capacity is modest (60%), while BPD oversight is weak (55%). Conversely, expectations for improvement are high (85%), particularly for broader public involvement and academic support. Novelty: The study integrates community-based legal education with governance principles to highlight the intersection of law, participation, and accountability in village administration. Implications: Strengthening technical capacity, expanding inclusive participation, and enhancing oversight mechanisms are crucial strategies for optimizing village regulation to achieve transparent, accountable, and responsive governance.Highlight : Community understanding of the function of village regulations is fairly good, but participation remains low. The capacity of village officials in regulation drafting needs strengthening. The supervisory mechanism of the Village Consultative Body (BPD) is not yet optimal and requires improvement. Keywords : Village Regulation, Village Governance, Good Governance, Legislation Theory, Participation